Cognitive aids in strategy - Sund, Kristian J.; Galavan, Robert J.; Gustafsson, Robin (Bingley, U.K. : Emerald Publishing Limited, 2023)
Strategy research and practice has a long tradition of using frameworks, models, tools, and processes to describe, and guide the strategy work of managers. These are the cognitive aids that guide cognition, i.e., the way managers make sense of the world. Why, and how, do these tools interact with cognition? The sixth volume in the New Horizons in Managerial and Organizational Cognition series examines cognitive aids in strategy. Cognitive aids of strategy have a profound impact on the way managers learn about, conceptualize, share, and enact strategy and strategies in their organizations, yet these aids are often presented without reference to the underlying cognitive theory that might explain why the aid is useful. Cognitive Aids in Strategy brings together contributions by twelve strategy scholars, reflecting on a range of cognitive aids and their theoretical foundations, focusing attention on the importance of cognitive aids in strategy, and inspiring further research. It represents a new horizon for the study of managerial and organizational cognition.
Chapter 1. What are cognitive aids in strategy? / Robin Gustafsson, Kristian J. Sund, and Robert J. Galavan -- Chapter 2. Opening up alternatives for managers stuck with complexity / Robert Wright -- Chapter 3. Testing the tool and not the theory / Nicolay Worren -- Chapter 4. Extending upper echelons theory: How evaluators influence signal interpretation and evaluation / Cole E. Short and Timothy D. Hubbard -- Chapter 5. Scenarios as cognitive aids: The necessary role of emotional labor in the cognition management of clients / Matthew Spaniol and Nicholas Rowland -- Chapter 6. Music as a metaphorical aid for strategic development / Arthur Turner -- Chapter 7. A neuroscience approach to entrepreneur pitch outcomes / Sohvi Heaton -- Chapter 8. Strategy work with artifacts: Neurocognitive advantages of visual sense-building / Robin Gustafsson -- Chapter 9. The relevance of social dynamics and dispositions on non-traditional aids to the strategic process / Davide Secchi.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Strategic planning; Business & Economics -- Strategic Planning; Business strategy